Burst Pressure Analysis on Corroded Pipeline Using Finite Element Method - Sormin, Mahadi Yahya; Hadiwidodo, Yoyok Setyo; Syahroni, Nur (International Journal of Offshore and Coastal Engineering (IJOCE), 2024)
The oil and gas industry includes exploration, extraction, production or processing, and transportation. One of the important activities in the oil and gas industry is the hydrocarbon transportation system. The most commonly used hydrocarbon transportation facility is the subsea pipeline. Pipes operating in a marine environment can easily corrode. Corrosion will cause a metal loss on the pipe surface and worsen the strength of the pipe. The thinning of the pipe surface due to corrosion will result in localized holes of varying depths and uneven shapes on the outer and inner surfaces. A burst pressure will occur if the internal pressure in the pipe with corrosion defects exceeds the allowable internal pressure limit. Therefore, to prevent burst pressure, it is necessary to evaluate the residual strength of the pipe in order to determine whether the defective pipe with working pressure can continue to operate safely or not. The internal pressure value calculation results are as follows: until the pipe fails, it is considered to burst using an FEA of 19.42 MPa. Meanwhile, the internal pressure value using standard codes DNV-RP-F101 is 18.76 MPa. For the effect of variations in the dimensions of the corrosion defect size, the most influential is the length and depth of the defect due to a decrease in the graph that does not fluctuate. The percentage differences between the failure pressure values resulting from rectangle and semi-ellipsoidal corrosion defects and the burst pressure values from the burst test experiments are 0.61% and 0.15%, respectively.